If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 = 3(x + -5) + -5x Reorder the terms: -27 = 3(-5 + x) + -5x -27 = (-5 * 3 + x * 3) + -5x -27 = (-15 + 3x) + -5x Combine like terms: 3x + -5x = -2x -27 = -15 + -2x Solving -27 = -15 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -27 + 2x = -15 + -2x + 2x Combine like terms: -2x + 2x = 0 -27 + 2x = -15 + 0 -27 + 2x = -15 Add '27' to each side of the equation. -27 + 27 + 2x = -15 + 27 Combine like terms: -27 + 27 = 0 0 + 2x = -15 + 27 2x = -15 + 27 Combine like terms: -15 + 27 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| -6+13x+-1x^2+-2x^3=0 | | y=-10-1 | | 75=d+15 | | 3x^2-4x+1024=0 | | -15n-20=12n-20 | | 4(8x-7)-7(6-7x)= | | 13x+30=3x+160 | | 72/(-9) | | 4z=-56 | | 8(10x+2)-(7+5x)= | | y=2x^3+12x^2-6x | | 6=13r | | 70=G-50 | | 5(v+5)-7v=15 | | -7+9=m-7 | | y+2(6)=0 | | 132-6x=4x+2x^2 | | -6u+2(u-5)=6 | | y+2(-4)=0 | | X^2-x+15=113 | | 30=5(y+4)-7y | | (x-2)(x+3)(1-2x)=0 | | 2x(4x+8y)= | | y+2(-6)=0 | | 12/6/2*3 | | 6y-20-y=19-3(-12y-18) | | 12/6/2.3 | | u-11=18 | | -w/3-4 | | 16z=40 | | -7x=23/74 | | 12/6/2x3 |